KONTRIBUSI SEKTOR PARIWISATA TERHADAP KEMSIKINAN DI PROVINSI SUMATERA BARAT - Revygusrivo Fitri Yenti Bur; Mike Triani (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to find out how the Influence the tourism sector contributes to poverty in the province of West Sumatera. The data used is secondary data in the form of a combination of time series and cross section from 2015 t0 2017, with documentation data collection techniques and library studies obtained from relevant institutions and agencies. The variables used are the regional revenue of the tourism sector, the number of hotel rooms, the number of small medium micro enterprises and poverty.The research methods used are: Random Effect Model (REM), (1) The regional income of the tourism sector contributessignificant. to reduction of poverty in the province of West Sumatera. (2) The number of hotel  contributes to reduction poverty in the province of West Sumatera but is not significant. (3) Micro small and medium enterprises contributes to reduction of poverty in the province of West Sumatera but is not significant. (4)The regional revenue of the tourism sector, the number of hotel room, and micro small and medium enterprises together has a signoficantt contribution to poverty inte the province of West Sumatera.